Novel design of drug delivery in stented arteries:A numerical comparative study - Mario Grassi; Giuseppe Pontrelli; Luciano Teresi; Gabriele Grassi; Lorenzo Comel; Alessio Ferluga; Luigi Galasso (Mathematical Biosciences and Engineering)
Implantation of drug eluting stents following percutaneoustransluminal angioplasty has revealed a well establishedtechnique for treating occlusions caused bythe atherosclerotic plaque.However, due to the risk of vascular re-occlusion,other alternative therapeutic strategiesof drug delivery are currently being investigated.Polymeric endoluminal pave stenting is an emerging technologyfor preventing blood erosion and for optimizing drug release.The classical and novel methodologies are compared througha mathematical model able to predict the evolution ofthe drug concentration in a cross-section of the wall.Though limited to an idealized configuration, the presentmodel is shown to catch most of the relevant aspects ofthe drug dynamics in a delivery system.Results of numerical simulations shows that a bi-layer gel paved stenting guarantees a uniform drug elution anda prolonged perfusionof the tissues, and remains a promising and effective techniquein drug delivery.